2017
DOI: 10.1007/s11051-017-3968-6
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoparticles as a modified diclofenac drug release system

Abstract: This study evaluated a modified nanostructured release system employing diclofenac as a drug model. Biodegradable chitosan nanoparticles were prepared with chitosan concentrations between 0.5 and 0.8% (w/v) by template polymerization method using methacrylic acid in aqueous solution. Chitosanpoly(methacrylic acid) (CS-PMAA) nanoparticles showed uniform size around 50-100 nm, homogeneous morphology, and spherical shape. Raw material and chitosan nanoparticles were characterized by thermal analysis, Fourier tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 73 publications
2
5
0
Order By: Relevance
“…Also, an exothermic peak at 296 • C referring to thermal decomposition of the chitosan pyranose ring was observed. Similar results were reported by literature [72,83]. For CS NP, DSC curve presented endothermic peaks at 57 • C and 282 • C corresponding to dehydration water and breakdown of electrostatic interactions between chitosan and TPP, respectively.…”
Section: Thermal Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…Also, an exothermic peak at 296 • C referring to thermal decomposition of the chitosan pyranose ring was observed. Similar results were reported by literature [72,83]. For CS NP, DSC curve presented endothermic peaks at 57 • C and 282 • C corresponding to dehydration water and breakdown of electrostatic interactions between chitosan and TPP, respectively.…”
Section: Thermal Analysissupporting
confidence: 89%
“…CS was degraded in three-stage process. On the first stage (35− 100 • C), a weight loss of 10 % referring to removal of water (T peak at 53.23 • C) was observed [72]. The second inflection point occurs at 296 • C and is related to the decomposition of the acetylated and deacetylated units and dehydration of the saccharide rings of the biopolymer, corresponding to around 50 % of the weight loss [63,73].…”
Section: Thermal Analysismentioning
confidence: 99%
“…For instance, Dias et al [ 57 ] reported a slow release rate of diclofenac diethylamine encapsulated in acetylated cashew gum nanoparticles. Despite the higher accumulated release reported by these authors (60%), the release profile observed in our work was more homogeneous, without the presence of burst effect and able to maintain a gradual and sustained release for more than 24 h. Compared to other polymeric nanostructured delivery systems for diclofenac, the CGP-PPG@diclofenac presented a performance similar to those from Yahia et al [ 16 ] and Duarte Junior et al [ 20 ], thus confirming the capacity of chitosan particles loaded with diclofenac sodium to provide a sustained release of this drug. Similarly, Yousefi et al [ 58 ] showed that magnetic@layered double hydroxide multicore@shell nanostructures were effective as controlled delivery systems for diclofenac and ibuprofen.…”
Section: Resultssupporting
confidence: 48%
“…In addition, diclofenac absorption is dependent of its dissolution rate and solubility, properties which will dictate its bioavailability [ 17 , 18 ]. Due to the short biological half-life and associated undesired side effects, diclofenac is an interesting candidate to be used in the development of controlled drug delivery systems for improving its therapeutic efficacy and patient compliance [ 15 , 19 , 20 ]. In the last years, diverse delivery systems have been proposed to increase the efficacy of diclofenac, with a number of studies focusing on the development of polymeric membranes and films [ 21 , 22 ], polymeric micro/nanoparticles [ 23 ], and hydrogels [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the numerous amino and hydroxyl groups, it can easily bind other chemicals such as drugs via establishing weak intermolecular interactions that significantly stabilize molecular complexes. Numerous experimental studies confirm the applicability of chitosan for controlled release of diclofenac [4][5][6][7][8]. The tissue engineering on the other hand exploits the porous structure and gel-forming properties of chitosan together with its high affinity to in vivo macromolecules [9].…”
Section: Introductionmentioning
confidence: 94%